Is the PentaBDE Replacement, Tris (1,3-dichloro-2-propyl) Phosphate (TDCPP), a Developmental Neurotoxicant? Studies in PC12 Cells - Dishaw, Laura V. (2011)
Organophosphate flame retardants (OPFRs) are used as replacements for the commercial PentaBDE mixture that was phased out in 2004. OPFRs are ubiquitous in the environment and detected at high concentrations in residential dust, suggesting widespread human exposure. OPFRs are structurally similar to neurotoxic organophosphate pesticides, raising concerns about exposure and toxicity to humans. This study evaluated the neurotoxicity of tris (1,3-dichloro-2-propyl) phosphate (TDCPP) compared to the organophosphate pesticide, chlorpyrifos (CPF), a known developmental neurotoxicant. We also tested the neurotoxicity of three structurally similar OPFRs, tris (2-chloroethyl) phosphate (TCEP), tris (1-chloropropyl) phosphate (TCPP), and tris (1,3-dibromopropyl) phosphate (TDBPP), and 2,2′,4,4′-tetrabromodiphenyl ether (BDE-47), a major component of PentaBDE. Using undifferentiated and differentiating PC12 cells, changes in DNA synthesis, oxidative stress, differentiation into dopaminergic or cholinergic neurophenotypes, cell number, cell growth and neurite growth were assessed. TDCPP displayed concentration-dependent neurotoxicity, often with effects equivalent to or greater than equimolar concentrations of CPF. TDCPP inhibited DNA synthesis, and all OPFRs decreased cell number, and altered neurodifferentiation. Although TDCPP elevated oxidative stress, there was no adverse effect on cell viability or growth. TDCPP and TDBPP promoted differentiation into both neuronal phenotypes, while TCEP and TCPP promoted only the cholinergic phenotype. BDE-47 had no effect on cell number, cell growth or neurite growth. Our results demonstrate that different OPFRs show divergent effects on neurodifferentiation, suggesting the participation of multiple mechanisms of toxicity. Additionally, these data suggest that OPFRs may affect neurodevelopment with similar or greater potency compared to known and suspected neurotoxicants.